2023
DOI: 10.1111/ctr.14914
|View full text |Cite
|
Sign up to set email alerts
|

Donor specific antibodies association with survival and adverse events after heart transplantation: A single center retrospective study between 2006 and 2021

Abstract: Objective Newly detected donor HLA‐specific antibodies (DSA) are historically known to be associated with reduced survival in heart transplant patients. Our objective is to clarify the modern incidence of DSA and determine its relationship with survival and MACE. Methods This retrospective study included all patients undergoing orthotopic heart transplantation at Harefield Hospital, London between January 1, 2006 and May 31, 2021. We identified patients who developed DSA at any point post heart transplantation… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

4
3
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
3
1

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(7 citation statements)
references
References 29 publications
4
3
0
Order By: Relevance
“…Development of DSA is frequently observed after HTx as approximately 25%–30% of patients develop de‐novo DSA within five years from HTx. The majority of these de‐novo DSAs are directed against HLA class II followed by a mixture against HLA class I and II 17–19 . In accordance with these data, we detected de‐novo DSA in 25% of our patients, mainly directed against HLA class II.…”
Section: Discussionsupporting
confidence: 90%
See 2 more Smart Citations
“…Development of DSA is frequently observed after HTx as approximately 25%–30% of patients develop de‐novo DSA within five years from HTx. The majority of these de‐novo DSAs are directed against HLA class II followed by a mixture against HLA class I and II 17–19 . In accordance with these data, we detected de‐novo DSA in 25% of our patients, mainly directed against HLA class II.…”
Section: Discussionsupporting
confidence: 90%
“…De novo DSAs are known to be associated with AMR, 3,20 CAV, 21–25 and mortality 19,24–27 . In keeping, DSA positive patients in our study had more advanced CAV, poorer graft function and higher levels of NT‐proBNP and troponin T. In our study, DSA positive patients with CAV at baseline showed a tendency towards more rapid progression of CAV.…”
Section: Discussionsupporting
confidence: 83%
See 1 more Smart Citation
“…53 Furthermore, we found that patients who were both class 1 and 2 DSA positive were at a significantly increased risk for being in the C4d+/DSA+ rather than C4d-/DSA+ group. This observation contributes to existing literature 8,17,20,54,55 and is important for HTx patients that become DSA positive as we did not find the majority of these patients (i.e., C4d-/DSA+ group) to be at increased risk for all cause death, cardiac death or retransplant, CAV, and cardiac allograft dysfunction compared to C4d-/DSA-patients. Further study of class 1 and 2 DSAs, including at a higher molecular resolution 22,56 , may provide additional insights of the risks specific DSAs pose to HTx patients.…”
Section: Discussionsupporting
confidence: 72%
“…However, it is dnD-SAs that are considered a major threat to transplant recipients [6,7]. In patients with heart transplant (HT), they have been associated with antibody-mediated rejection (AMR) [6,8], cardiac allograft vasculopathy (CAV) [9,10], graft dysfunction [11], and mortality [12][13][14]. They represent one of the main concerns of the HT scientific community because of their tight relationship with long-term outcomes, which have remained barely unchanged over recent years [15].…”
Section: Introductionmentioning
confidence: 99%